2013
DOI: 10.1186/1754-6834-6-12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of replacing polyol by organosolv and kraft lignin on the property and structure of rigid polyurethane foam

Abstract: BackgroundLignin is one of the three major components in plant cell walls, and it can be isolated (dissolved) from the cell wall in pretreatment or chemical pulping. However, there is a lack of high-value applications for lignin, and the commonest proposal for lignin is power and steam generation through combustion. Organosolv ethanol process is one of the effective pretreatment methods for woody biomass for cellulosic ethanol production, and kraft process is a dominant chemical pulping method in paper industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(151 citation statements)
references
References 19 publications
4
144
0
3
Order By: Relevance
“…The alteration in the cell structure may be due to the fact that high lignin content affected the cell nucleation process in the preparation of PU foams [30]. Similar results were also found by Pan and Saddler [17], who reported that the increase of ethanol organosolv lignin ratio in petroleum-based polyol resulted in particularly large cells (bubbles). However, this finding regarding cell diameter was quite different from Luo et al [3].…”
Section: Morphological Structuressupporting
confidence: 76%
See 2 more Smart Citations
“…The alteration in the cell structure may be due to the fact that high lignin content affected the cell nucleation process in the preparation of PU foams [30]. Similar results were also found by Pan and Saddler [17], who reported that the increase of ethanol organosolv lignin ratio in petroleum-based polyol resulted in particularly large cells (bubbles). However, this finding regarding cell diameter was quite different from Luo et al [3].…”
Section: Morphological Structuressupporting
confidence: 76%
“…With higher lignin content (15%), the mechanical properties of the foam were decreased, probably due to the lignin macromolecules agglomerating into segments, which reduced the uniform distribution of lignin in the foam. This will result in significant changes in the cellular structure and weaken the strength of the foam [17].…”
Section: Apparent Density and Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, of the four lignins tested in this study, L2 was the most degraded from its original form. Lignins with a fair amount of hydroxyl (phenolic and aliphatic) and carboxyl groups can potentially replace polyols in polyurethane production (Pan and Saddler 2013). …”
Section: Elemental Composition Of Ligninmentioning
confidence: 99%
“…Most of the lignin extracted from pulp and paper operations is burned during pulp-spent liquor treatment. This offers energy recovery and regeneration of pulping chemicals with less than 2% recovered for utilization as a chemical product [137] [138]. However, the amount of lignin produced exceeds the requirements for energy generation.…”
Section: Lignin Based Polyurethane Adhesivementioning
confidence: 99%